2016
DOI: 10.1097/rhu.0000000000000424
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatologists and Ophthalmologists Differ in Treatment Decisions for Ocular Behçet Disease

Abstract: Physician decision making is influenced by medical specialty and concerns regarding cost and prior authorization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…First U.S. patients seen by rheumatologists may have more joint complaints, as has been described in other studies [ 7 , 13 ], and biologics would be well-suited for these symptoms. Second, insurance systems are likely different between the U.S. and Eastern countries, which may make biologic medications more accessible in the U.S. Rheumatologists preferred the choice of anti-TNFi therapy over conventional DMARDs for BD when cost and prior authorization issue were not a concern [ 29 ]. Third, U.S. primary care physicians may not be as familiar with this rare disease; thus, only the most complicated patients may be diagnosed and treated by rheumatologists.…”
Section: Discussionmentioning
confidence: 99%
“…First U.S. patients seen by rheumatologists may have more joint complaints, as has been described in other studies [ 7 , 13 ], and biologics would be well-suited for these symptoms. Second, insurance systems are likely different between the U.S. and Eastern countries, which may make biologic medications more accessible in the U.S. Rheumatologists preferred the choice of anti-TNFi therapy over conventional DMARDs for BD when cost and prior authorization issue were not a concern [ 29 ]. Third, U.S. primary care physicians may not be as familiar with this rare disease; thus, only the most complicated patients may be diagnosed and treated by rheumatologists.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have shown that ophthalmologists and rheumatologists may have different preferences, based on costs, sub‐specialization and hospital authorization. All these factors emphasize the complexity of therapeutic decision‐making in these patients and the importance of combining expertise (Ozzello et al 2016; Palestine et al 2016). The current study included many patients in reproductive age, whose possible desire to have children in the near future had to be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…This study specifically looked at adherence barriers in a sample of pediatric patients. The literature on medication selection by the treating physician based on cost has disparate conclusions depending on the anatomic location of uveitis being treated, which ranges from no effect to strictly choosing therapy based on price [10][11][12]. Understanding that there are financial constraints to treatment and adherence in patients with uveitis is only half of the problem.…”
Section: Introductionmentioning
confidence: 99%